2021
DOI: 10.1024/0300-9831/a000653
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of chrysin against carbon tetrachloride-induced kidney and liver tissue damage in rats

Abstract: The aim of this study was to investigate the possible protective effects of chrysin on oxidative status and histological alterations against carbon tetrachloride (CCl4)-induced liver and kidney tissue in rats. The animals were randomly divided into four groups; the control, chrysin (100 mg/kg), CCl4 (0.5 ml/kg) and chrysin + CCl4 groups. Liver and kidney injuries were assessed by biochemical and histopathological examinations. The levels of malondialdehyde (MDA), reduced glutathione (GSH), and superoxide dismu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…[16] Furthermore, Chy protected against carbon tetrachloride-induced hepatorenal damage by increasing antioxidant enzymes activity (SOD and GSH levels) and decreasing TNF-α and MDA levels. [39] Our results collectively suggested that the protective effect of Chy against CyC-induced cardiac damage may be associated with its antioxidant and anti-inflammatory properties.…”
Section: Discussionsupporting
confidence: 56%
“…[16] Furthermore, Chy protected against carbon tetrachloride-induced hepatorenal damage by increasing antioxidant enzymes activity (SOD and GSH levels) and decreasing TNF-α and MDA levels. [39] Our results collectively suggested that the protective effect of Chy against CyC-induced cardiac damage may be associated with its antioxidant and anti-inflammatory properties.…”
Section: Discussionsupporting
confidence: 56%
“…This result coincided with a remarkable attenuation of the cell degeneration in H&E staining. The effect of chrysin to on liver function marker enzymes is previously reported [ 33 , 50 54 ] and could be explained in terms of its antioxidant characteristics [ 25 ].…”
Section: Discussionmentioning
confidence: 94%
“…The fructose-induced inflammatory response was markedly ameliorated by chrysin, particularly with the dose of 50 mg/kg. Similarly, several studies demonstrated the hepatoprotective activity of chrysin by reducing the production of inflammatory cytokines [ 33 , 50 , 52 , 63 , 64 ]. This effect could be attributed to the suppression of NF- κ B.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, this process consequently induces oxidative stress in body tissues, especially in the liver, because the main metabolism center of nicotine is the liver [ 6 ]. In the end, the obtained product of lipid peroxidation is an active and highly reactive aldehyde compound named as malondialdehyde (MDA), which can be used as an indicator to evaluate oxidative stress [ 7 ].…”
Section: Introductionmentioning
confidence: 99%